2021
DOI: 10.1111/cla.12456
|View full text |Cite
|
Sign up to set email alerts
|

A reconsideration of inapplicable characters, and an approximation with step‐matrix recoding

Abstract: Evidence for phylogenetic analysis comes in the form of observed similarities, and trees are selected to minimize the number of similarities that cannot be accounted for by homology (homoplasies). Thus, the classical argument for parsimony directly links homoplasy with explanatory power. When characters are hierarchically related, a first character may represent a primary structure such as tail absence/presence and a secondary (subordinate) character may describe tail colour; this makes tail colour inapplicabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(82 citation statements)
references
References 55 publications
0
67
0
Order By: Relevance
“…We made extensive use of contingent (or reductive) coding, which means that characters are hierarchically dependent on each other. Despite potential problems, this is currently the best available option for this study [ 90 92 ]. Although there has been recent progress in the development of methods dealing with inapplicable characters, most of these are not yet available for Bayesian inference, as they require different algorithms or coding strategies [ 92 94 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We made extensive use of contingent (or reductive) coding, which means that characters are hierarchically dependent on each other. Despite potential problems, this is currently the best available option for this study [ 90 92 ]. Although there has been recent progress in the development of methods dealing with inapplicable characters, most of these are not yet available for Bayesian inference, as they require different algorithms or coding strategies [ 92 94 ].…”
Section: Methodsmentioning
confidence: 99%
“…Despite potential problems, this is currently the best available option for this study [ 90 92 ]. Although there has been recent progress in the development of methods dealing with inapplicable characters, most of these are not yet available for Bayesian inference, as they require different algorithms or coding strategies [ 92 94 ]. Another recently developed alternative method using structured Markov models is computationally intensive for large hierarchies and needs further testing in empirical datasets [ 95 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ED has often been coded using inapplicable characters, which are then analyzed under parsimony or likelihood-based methods. In parsimony, the inapplicable coding was shown to be inappropriate (Maddison, 1993), which encouraged the development of new parsimony-based methods to handle the ED (Brazeau et al, 2019; Hopkins and St. John, 2021; Goloboff et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Most Markov models in phylogenetics treat characters as independent entities and, thereby, cannot be applied to ED. The study of Goloboff et al (2021) has recognized this fact that possibly led the authors to conclude that probabilistic treatment of ED requires new algorithms for likelihood calculation. They suggested that ED cannot be described with infinitesimal rate matrices ( Q ) alone, used for specifying MC evolution.…”
Section: Deriving Embedded Dependency Modelsmentioning
confidence: 99%
See 1 more Smart Citation